Cu Nanoparticles for Improving the Mechanical Performances of Oil Palm Empty Fruit Bunch Fibers as Analyzed by Weibull Model - Chowdhury, M. N. K.; M. F., Fina; Khan, Maksudur R.; Beg, M. D. H. (Springer Berlin Heidelberg, 2013)
Cu nanoparticles (CuNPs) were impregnated in oil palm empty fruit bunch (EFB) fibers via the cationization process. The fiber surface modification by CuNPs has been verified by Fourier-transformed infrared spectroscopy, field emission scanning electron microscopy and energy dispersive X-ray study. Mechanical properties were measured by the tensile test and analyzed by the Griffith and the Weibull models. The 10 mm length EFB fiber modified by CuNPs shows an increment in characteristic strength ( σ0) and modulus (Y 0) by about 20 and 10 % compared to the unmodified fiber, as assessed by the Weibull model. This improvement in mechanical properties is associated with the incorporation of CuNPs in the fibers. Weak-link scaling model has been applied to predict the mechanical properties of unknown fiber.